Celecoxib/Cyclodextrin Eye Drop Microsuspensions: Evaluation of In Vitro Cytotoxicity and Anti-VEGF Efficacy for Retinal Diseases - Phatsawee Jansook; Hay Man Saung Hnin Soe; Rathapon Asasutjarit; Theingi Tun; Hay Marn Hnin; Phyo Darli Maw; Tanapong Watchararot; Thorsteinn Loftsson (MDPI AG, 2023)
Celecoxib (CCB), a cyclooxygenase-2 inhibitor, is capable of reducing oxidative stress and vascular endothelial growth factor (VEGF) expression in retinal cells and has been shown to be effective in the treatment of diabetic retinopathy and age-related macular degeneration. However, the ocular bioavailability of CCB is hampered due to its very low aqueous solubility. In a previous study, we developed 0.5% (w/v) aqueous CCB eye drop microsuspensions (MS) containing randomly methylated β-cyclodextrin (RMβCD) or γ-cyclodextrin (γCD) and hyaluronic acid (HA) as ternary CCB/CD/HA nanoaggregates. Both formulations exhibited good physicochemical properties. Therefore, we further investigated their cytotoxicity and efficacy in a human retina cell line in this study. At a CCB concentration of 1000 μg/mL, both CCB/RMβCD and CCB/γCD eye drop MS showed low hemolysis activity (11.1 ± 0.3% or 4.9 ± 0.2%, respectively). They revealed no signs of causing irritation and were nontoxic to retinal pigment epithelial cells. Moreover, the CCB eye drop MS exhibited significant anti-VEGF activity by reducing VEGF mRNA and protein levels compared to CCB suspended in phosphate buffer saline. The ex vivo transscleral diffusion demonstrated that a high quantity of CCB (112.47 ± 37.27 μg/mL) from CCB/γCD eye drop MS was deposited in the porcine sclera. Our new findings suggest that CCB/CD eye drop MS could be safely delivered to the ocular tissues and demonstrate promising eye drop formulations for retinal disease treatment.